Tombs visited by women and ceremonies performed by women (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article is about women’s graves and women’s ceremonies in the southwest of the Fergana Valley. According to the population of the southwest of the Fergana Valley, there are rites and rituals based on the consecration of the forces of nature. Sacred trees, springs, mountains and rocks were considered sacred, along with rituals and ceremonies that contained remnants of beliefs associated with Zoroastrianism and Mother Umai. Like Uyutku, the original essence has been preserved, family rituals, mixed with Islamic traditions, have been preserved. The most enduring remnants of rituals and ceremonies are those organized by women during pilgrimages to holy places. Based on an analysis of the complex of rituals performed, we were informed that when visiting holy places and performing ceremonies, women perform actions related to pre-Islamic beliefs. Methods: mainly theoretical and empirical research methods were used during the study of women’s shrines and women ceremonies. Conclusion: kyrgyz people in the south-west of the Fergana Valley have their ethnocultural features determined through the tombs where women go and the ceremony held only by women.
Keywords: Mother Umai, women’s grave, pilgrimage, Biseishenbi, Mushkul Kishot, ritual